Translocation of tropical peat surface to deeper soil horizons under compaction controls carbon emissions in the absence of groundwater - Samuel, Marshall Kana; Evers, Stephanie (Frontiers in Soil Science, 2024)
Compaction is recognized as an effective method for mitigating the risk of fires by enhancing soil moisture levels. This technique involves restricting peat pore spaces through compaction, facilitating improved capillary action for water retention and rehydration. The compaction of tropical peatlands, while beneficial for fire prevention, has the potential to influence biogeochemical processes and subsequent carbon emissions. The magnitude of compaction and groundwater level are strongly coupled in such environments, making it difficult to distinguish the control of physicochemical properties. Therefore, this study seeks to understand how peat compaction affects its properties, carbon emissions, and their relationship, with a focus on geophysical processes. Intact peat samples were collected from a secondary peat swamp forest and an oil palm plantation in Selangor, Peninsular Malaysia. Compaction treatments were applied to achieve three levels of volume reduction. CO2 and CH4 emissions were measured using an automated gas analyzer, and the physicochemical properties of the peat were determined. The results revealed that mechanical compaction significantly altered the physicochemical properties of the secondary forest peat, displaying an opposite pattern to the oil palm plantation, particularly regarding total nitrogen and sulfur. Moreover, the average reduction percentage ratio of CO2 emissions (from 275.4 to 182.0 mg m -2 hr -1 ; 33.9%) to CH4 uptakes (from -17.8 to -5.2 µg m -2 hr -1 ; 70.1%) (~1:2) indicated distinct stages of decomposition and translocation of less decomposed peat to deeper layers due to compaction, predominantly in secondary peat swamp forest samples. The oil palm plantation samples were unaffected by compaction in terms of physicochemical properties and carbon emissions, indicating the ineffectiveness of this approach for reducing fire risk in already drained systems. This study underscores the necessity of understanding the effects of compaction in the absence of groundwater to accurately evaluate the widespread application of this technique.